Communities in Motion: preserving heritage, legacies and learning from centres of Black organising and activism - Robinson, Lisa J (2025)
This thesis assembles the histories of three Nottingham centres of Black community organising and activism operating between the 1980s to the early 2000s: Ukaidi, African Caribbean Families and Friends (ACFF), and the Organisation for Sickle Cell Anaemia Research (OSCAR). Whilst the centres have physically disappeared, they live on in the memories of those who worked at and used them. The thesis evokes the centres’ afterlives through oral histories and archival research. It charts how the centres sustained Black life in this city and beyond. It suggests how heritages, legacies, and learnings might be preserved for the benefit of future generations of organisers and activists, here in Nottingham, across the UK, and throughout the Black diaspora. Ultimately the thesis asks the hyper-local question: is there a need for a Centre of Black Life in Nottingham?